N-Benzylisatin - H. Braband; A. Roodt; M. Schutte; H. G. Visser (Acta Crystallographica Section E, 2012)
In the title compound, C15H11NO2, two C—H...O hydrogen bonds are observed in the crystal structure, as well as π–π stacking with a centroid–centroid distance of 3.623 (2) Å. The planarity of the two ring systems is illustrated by very small deviations of all the atoms from these planes [largest deviations = 0.003 (3) and 0.010 (3) Å for the phenyl and fused-benzene rings, respectively]. The dihedral angle between these two planes is 77.65 (9)°.